The Effect of Euphemism as Teaching Expressions on EFL University Students’ Vocabulary Repertoire - Khalil, Yaman Muthana; Mohammed, Ibtisam Jassim (Journal of Tikrit University for Humanities, 2024)
Neglecting vocabulary hampers academic success as students struggle with comprehension, expression, and participation, impacting their university and future achievements. This study aims at: Finding out the effect of Euphemism as teaching expressions on students’ performance in the vocabulary; finding out the effect of Euphemism as teaching expressions on students’ performance in distinguishing vocabulary; finding out the effect of Euphemism as teaching expressions on students’ performance in producing vocabulary. A sample consists of 100 fourth year university students from Tikrit university. A sample has been randomly selected and divided into two equal groups, i.e., experimental and control groups. They have been equalized in age, gender, pretest, parents’ academic attainment, and their previous year scores in novel. The two groups have been taught the same instructional material for twelve weeks. The posttest has been constructed, validated, its reliability obtained, its items analyzed, and then applied to the two groups of students at the end of the instructional period of the current study. The obtained results are as follows: There is statistically significant difference between the experimental and control groups in vocabulary repertoire and in favor of the experimental group; there is statistically significant difference between experimental and control groups in distinguishing vocabulary and the in favor of the experimental group also; there is statistically significant difference between experimental and control groups in production of vocabulary and in favor of the latter.